Hypoallergen Peanut Lines Identified Through Large-Scale Phenotyping of Global Diversity Panel: Providing Hope Toward Addressing One of the Major Global Food Safety Concerns - Pandey, Arun K.; Sudini, Hari K.; Upadhyaya, Hari D.; Varshney, Rajeev K.; Pandey, Manish K. (Frontiers in Genetics, 2019)
Peanut allergy is one of the serious health concern and affects more than 1% of the world’s population mainly in Americas, Australia and Europe. Peanut allergy is sometimes life-threatening and adversely affect the life quality of allergic individuals and their families. Consumption of hypoallergenic peanuts is the best solution, however, not much effort has been made in this direction for identifying or developing hypoallergenic peanut varieties. A highly diverse peanut germplasm panal was phenotyped using a recently developed monoclonal antibody-based ELISA protocol to quantify five major allergens. Results revealed a wide phenotypic variation for all the five allergens studied i.e., Ara h 1 (4 – 36833 µg/g), Ara h 2 (41-77041 µg/g), Ara h 3 (22 - 106765 µg/g), Ara h 6 (829 - 103892 µg/g) and Ara h 8 (0.01 – 70.12 µg/g). The hypoallergenic peanut genotypes with low levels of allergen proteins for Ara h 1 (4 µg/g), Ara h 2 (41 µg/g), Ara h 3 (22 µg/g), Ara h 6 (829 µg/g) and Ara h 8 (0.01 µg/g) have paved the way for their use in breeding and genomics studies. In addition, these hypoallergenic peanut genotypes are available for use in cultivation and industry, thus opened up new vistas for fighting against peanut allergy problem across the world.